De Roma a Angostura : acercamiento al pensamiento político de Simón Bolívar a través de sus escritos durante las fases iniciales del proceso de Independencia : primera parte (1805-1813) (2016)
ABSTRACT: This article approaches the political thought of Simón Bolívar through an analysis of his most important documents written in the period 1805-1819, and of the context in which they were written. The article follows Bolívar’s life, from his birth, through his education and political success up to his achieving the status of the Liberator at his glorious reception in Caracas after the successful Admirable Campaign, just a few months before his spectacular fall from grace and the inglorious years that followed. The article traces his victories and defeats throughout this period, focusing on how they formed his character and contributed to his exaltation amongst his comrades for his self-sacrifice and courage.